Analisis Sistem Informasi Akuntansi Persediaan Barang Dagang CV. Citra Selaras Yamaha Motor Bau-Bau - Rafida Bangki, Ristian, Dian Mayafaty Rauf (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
This article is the result of research analyzing the merchandise inventory accounting information system at CV. Citra Selaras Yamaha Motor Baubau, where the aspect of the merchandise inventory accounting information system is the Sales Accounting Information System, purchase accounting information system, and cash receipts accounting information system. This research aims to determine and analyze the merchandise inventory accounting information system applied to CV. Citra Harmony Yamaha Motor Baubau. This research is qualitative research. This research uses interviews, observation and documentation in data collection. The results of this research indicate that the merchandise inventory accounting information system is effective and quite good which can be seen in the procedures that form the merchandise inventory system, namely by the division of tasks and responsibilities which are equipped with documents and inventory recording using the perpetual method by applying computerized system and has implemented the Authority's system in accordance with applicable accounting standards, namely the sales accounting information system, purchasing accounting information system and cash receipts accounting information system.